Hepatic arterial infusion chemotherapy combined with anti-PD-1/PD-L1 immunotherapy and molecularly targeted agents for advanced hepatocellular carcinoma: a real world study - Zhang, Weihao; Zhang, Kai; Liu, Changfu; Gao, Wei; Si, Tongguo; Zou, Qiang; Guo, Zhi; Yang, Xueling; Li, Mei; Liu, Dongming; Mu, Han; Li, Huikai; et al. (Frontiers in Immunology, 2023)
Background: Molecular targeted therapy combined with immunotherapy significantly improves the prognosis of patients with advanced liver cancer. Additionally, hepatic arterial infusion chemotherapy (HAIC) can improve the prognosis of patients with advanced liver cancer. This real-world study aimed to evaluate the clinical efficacy and safety of HAIC combined with molecular targeted therapy and immunotherapy in the treatment of primary unresectable hepatocellular carcinoma (uHCC).Methods: A total of 135 patients with uHCC were enrolled in this study. Progression-free survival (PFS) was the primary endpoint. The efficacy of the combination therapy was assessed based on the modified Response Evaluation Criteria in Solid Tumors (mRECIST) guidelines. Overall survival (OS), adverse events (AEs) and surgical conversion rate were the secondary endpoints. Univariate and multivariate Cox regression analyses were performed to examine independent prognostic factors. For sensitivity analysis, inverse probability weighting (IPW) was used to balance the influence of the tested confounding factors between groups to verify the robustness of conversion surgery for survival benefits. Results:The median number of therapies was three. Approximately 60% of the patients had portal vein tumour thrombosis (PVTT). The most common targeted drugs were lenvatinib and bevacizumab, whereas the most common immunotherapy drug was sintilimab. The overall objective response rate (ORR) was 54.1%, and the disease control rate (DCR) was 94.6%. A total of 97 (72%) patients experienced AEs of grades 3–4. Fatigue, pain and fever were the most common symptoms of grade 3-4 AEs. The median PFS was 28 months and 7 months in the successful and unsuccessful conversion groups, respectively. The median OS was 30 months and 15 months in the successful and unsuccessful conversion groups, respectively. Successful conversion surgery, number of interventions, PVTT and total bilirubin levels were independent prognostic factors for OS. After IPTW, no standardised differences exceeding 0.1 were found. IPW-adjusted Kaplan–Meier curves showed that successful conversion surgery was an independent prognostic factor for both PFS and OS. Conclusion: Patients with primary uHCC undergoing HAIC combined with immunotherapy and molecular targeted therapy have a higher tumour regression rate and the side effects are manageable. Patients undergoing surgery after combination therapy have survival benefits.